Strategic Code-Mixing in Maudy Ayunda’s Educational YouTube Content. - Efandi Yakob; Ni Made Diana Erfiani; Yohanes Octovianus Lesu Awololon; Putu Chrisma Dewi (Universitas Islam Negeri Palopo, 2026)
Code-mixing has become a strategic linguistic resource through which bilingual public figures construct social identities in digital environments. However, despite the growing number of studies on code-mixing in entertainment-oriented digital discourse, limited attention has been given to educational YouTube monologues as sites of intellectual identity construction. This study investigates the structural patterns of code-mixing employed by Maudy Ayunda in her educational YouTube content and explores how these patterns contribute to the construction of an intellectual digital identity, which refers to the projection of expertise, credibility, and intellectual authority through bilingual language practices. Drawing on Muysken’s (2000) typology of code-mixing, this study adopts a qualitative descriptive approach using a structural sociolinguistic framework. The data consist of 70 instances of code-mixing extracted from the orthographic transcript of the video “The Power of Now: Stop Worrying, Start Being Present – Maudy Ayunda’s Book List” (2026). The findings reveal three types of code-mixing, namely insertion (48 instances), alternation (16 instances), and congruent lexicalisation (6 instances), with insertion emerging as the dominant pattern. The frequent use of insertion indicates the speaker’s tendency to maintain conceptual precision by incorporating English academic and psychological terminology into Indonesian discourse. The findings also demonstrate that code-mixing functions not merely as a linguistic phenomenon but as a strategic resource for constructing an intellectual and globally oriented persona in educational digital communication. Therefore, this study contributes to digital sociolinguistics by extending discussions of code-mixing beyond entertainment-oriented discourse and highlighting its role in identity construction within contemporary online educational environments.